Influence of radiant exposure values from two third generation LED curing units on polymerization profile and microhardness of orthodontic composite under ceramic and metallic brackets - Andrés Fernando Montenegro ARANA; Barbara JUSTUS; Andrés DÁVILA-SÁNCHEZ; Michele de Oliveira SUGAHARA; Ulisses COELHO; Paulo Vitor FARAGO; Cesar ARRAIS (Dental Press Editora, 2021)
ABSTRACT Introduction: Third generation of LED light curing units might be used in short exposure periods for orthodontic brackets bonding. Objective: This study evaluated the effect of the different radiant exposure (RE) values: Manufacturers' instructions (MI), ½ MI, 1/4 MI and Turbo mode. Two third-generation LED curing units were used: VALO® and Bluephase 20i® . The degree of conversion (DC) and Vickers hardness (VHN) of an orthodontic composite (OC) (Transbond XT) under metallic (MB) or ceramic brackets (CB) were measured. Methods: OC was applied to the bracket base, which was then placed over an attenuated total reflectance (ATR) table coupled to an infrared light spectroscope, or to a glass surface for the VHN analysis. The specimens were light-cured and DC values were calculated. The VHN was obtained in a microhardness tester. The data were analyzed with 2-way ANOVA followed by Tukey's post-hoc test (pre-set α=0.05). Linear regression analysis evaluated the relationship between RE values and dependent variables. Results: CB allowed higher DC and VHN values than MB (p< 0.001). No significant difference was noted among groups when CB were used. For MB, MI groups showed the highest DC and VHN values. A significant, but weak relationship was found between delivered RE values and dependent variables. Conclusions: The decrease in RE values from third generation LED CU did not jeopardize the DC values when CB were used, but can compromise DC and VHN values when MB are used.